Desain dan Implementasi Web Proxy dan VPN Akses (Studi Kasus di Undip) - Fatchur Rochim, Adian; Satria Martiyanto, Andrian (JURNAL SISTEM KOMPUTER, 2011)
The development of computer and network technologies lead many organizations to expand its network. The intranet network is used initially to connect clients with geographically dispersed enterprise networks, but when it is need a more extensive and huge network intranets are not possible anymore, it is necessary development of a secure private network that uses Internet network. Methodology of research for this final task include the study of literature, design systems, and testing of the system. In the literature study used research methods from the literature study reference books that are related. The design of this final task using OpenVPN and Glype Proxy to access the local network from the Internet. Last is the testing of this network system, where in this stage the network system will be tested in order to create a reliable network and secure. The result obtained is a network system that allows users from outside the network can access some or all services available on the local network as still in a network, from anywhere via the Internet. For Internet users to become members of this private network they must go through the process of authentication, the data available on the private network is encrypted so it can not be opened except by the members of this private networks.Index Terms—Internet, intranet, VPN, Web Proxy